Influence of peer learning, self-regulatory learning, and mathematics interest on mathematics performance - Michael, Batsa; Arthur, Yarhands Dissou; Asare, Bright (International Journal of Didactic Mathematics in Distance Education, 2025)
The current study examined the influence of peer learning, self-regulatory learning, and mathematics interest on mathematics performance. The study adopted descriptive survey using questionnaire for the data collection. 320 students were sampled from a total population of 1600 students using stratified sampling and simple random sampling techniques. The data collected was analysed using Structural equation modeling to examined the hypothesized paths. Based on the data analysis, peer learning, self-regulatory learning, and mathematics interest had a direct positive and statistically significant impact on mathematics performance. The study explores the impact of peer learning, self-regulatory learning, and mathematics interest on students' performance, offering insights for effective instructional strategies and policy interventions. Finally, the study suggests incorporating structured peer-learning activities, self-regulatory learning strategies, engaging mathematical contexts, and professional development programs for teachers to enhance student autonomy and interest in mathematics.